1996
DOI: 10.1007/bf02331380
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical evidence of PDGF- and TGF-β-like molecules in invertebrate and vertebrate immunocytes: An evolutionary approach

Abstract: Immunoreactive platelet-derived growth factor-AB and transforming growth factor-beta 1 were demonstrated in invertebrate and vertebrate immunocytes by an immunocytochemical procedure. These factors are only present in phagocytic cells among invertebrate immunocytes, whereas in vertebrate immunocytes they are found in monocytes, granulocytes, lymphocytes, thrombocytes and platelets. These results, in agreement with previous reports, represent further evidence in favour of the hypothesis that Nature has followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
23
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 46 publications
5
23
0
Order By: Relevance
“…The present study provided evidence that the hemocytes of ticks possess the PDGF-AB-, TGF-β-and PDGF-receptor-α-like molecules and a finding that is in agreement with Franchini et al [6] suggesting that immunocytes from invertebrates and lower and higher vertebrates, including man, show the presence of similar molecules immunoreactive to anti-PDGF-AB and anti-TGF-β1 antibodies. According to Ottaviani et al [17], the use of computer-assisted microscopic image analysis demonstrated that PDGF-AB and TGF-β1 induced changes in the cell shape of hemocytes from a marine mollusc.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The present study provided evidence that the hemocytes of ticks possess the PDGF-AB-, TGF-β-and PDGF-receptor-α-like molecules and a finding that is in agreement with Franchini et al [6] suggesting that immunocytes from invertebrates and lower and higher vertebrates, including man, show the presence of similar molecules immunoreactive to anti-PDGF-AB and anti-TGF-β1 antibodies. According to Ottaviani et al [17], the use of computer-assisted microscopic image analysis demonstrated that PDGF-AB and TGF-β1 induced changes in the cell shape of hemocytes from a marine mollusc.…”
supporting
confidence: 93%
“…It has also been reported that PDGF-AB and TGF-β1 from the immunocytes of an invertebrate, the marine mollusc Mytilus galloprovincialis, caused change in cellular shape and induced migration in a chemotactic manner [6,17]. Furthermore, the presence of PDGF-receptor-α-, -β-and TGF-β-receptorlike molecules on the plasma membranes in the immunocytes of M. galloprovincialis was demonstrated by an immunocytochemical procedure [6,14,17].…”
mentioning
confidence: 99%
“…They are present in the same immunocytes, i.e. cells with phagocytic activity [5], are able to influence hemocyte migration and increase phagocytic capacity [6] and can intervene in the stress response with either an inhibiting or inducing effect.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the presence of PDGF-and TGFß-like molecules in several invertebrate immunocytes, including molluscs, has been demonstrated [5]. Moreover, PDGF-AB and TGF-ßl are able to stimulate cell migration and enhance phagocytosis in molluscan hemocytes [6].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of immune-reactive molecules to TGF-b 1 has been detected in immunocytes from molluscs Planorbarius corneus, Viviparus ater, Viviparus contectus, Lymnaea stagnalis, Mytilus galloprovincialis, in the insects Calliphora vomitoria and in the annelids Eisenia foetida (Franchini et al, 1996;Ottaviani et al, 2000). In invertebrates, TGF-b1 affects immunocyte and human monocyte migration in dose-correlated fashion and induces hemocytes to migrate in a chemotactic manner (Ottaviani et al, 1997a).…”
Section: Introductionmentioning
confidence: 99%